2018
DOI: 10.5219/900
|View full text |Cite
|
Sign up to set email alerts
|

Impact of somatic cell count and lameness on the production and composition of ewe's milk

Abstract: High somatic cell count (SCC) in milk and lameness are two very serious problems on the farms. The aim of the study was to evaluate the impact of lameness, SCC, month and order of entry into the milking parlour on the milk production and its composition. The relationship between lameness and SCC and their impact on the order of entry was also evaluated. The experiment was carried out at the farm, located in northern Slovakia. The farm keeps sheep crossbred of Improved Valachian and Lacaune. Milking was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
(6 reference statements)
1
1
0
1
Order By: Relevance
“…In observed months we found out significant decrease content of lactose in SCC group with SCC ≥1,000 × 10 3 cells/ml (4.4 ±0.04%) in compared to SCC group with low SCC <200 × 10 3 cells/ml (4.8 ±0.03%) and SCC group with SCC ≥200 <400 × 10 3 cells/ml (4.7 ±0.03%) (P <0.001). Lower lactose content in milk with high SCC was recorded in study published by Baranovič et al (2018). Also we detected significant impact of months of observation on decline content of lactose (P <0.001) ( Table 1).…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…In observed months we found out significant decrease content of lactose in SCC group with SCC ≥1,000 × 10 3 cells/ml (4.4 ±0.04%) in compared to SCC group with low SCC <200 × 10 3 cells/ml (4.8 ±0.03%) and SCC group with SCC ≥200 <400 × 10 3 cells/ml (4.7 ±0.03%) (P <0.001). Lower lactose content in milk with high SCC was recorded in study published by Baranovič et al (2018). Also we detected significant impact of months of observation on decline content of lactose (P <0.001) ( Table 1).…”
Section: Resultssupporting
confidence: 61%
“…Mastitis decreased milk yield up to 25% (Cuccuru et al, 2011). Also our previous study showed negative effect of somatic cells counts (SCC) on milk yield and its composition (Margetín et al, 2013;Baranovič et al, 2018;Tančin et al, 2017a).…”
Section: Introductionmentioning
confidence: 92%
“…), pri obsahu bielkovín bol pozorovaný signifikantný rozdiel aj medzi 2. a poslednou obrátkou. Nakoľko zvieratá chované na tejto farme mali počas našich meraní veľmi nízky PSB a množstvo zvierat s PSB vyšším ako 300 000 buniek/mL bolo nízke, zvieratá boli rozdelené do skupín podľa PSB (Tabuľka 3) prísnejšie ako v iných štúdiách (Martí de Olives et al, 2015; Baranovič et al, 2018;Sutera et al, 2018). Napriek tomu, sa nezistili žiadne signifikantné rozdiely medzi hodnotenými skupinami v zložení mlieka a ani v jeho množstve.…”
Section: Výsledky a Diskusiaunclassified